2022
DOI: 10.3389/fpls.2022.867778
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Symbiosis Triggers Local Resistance in Citrus Plants Against Spider Mites

Abstract: Citrus plants are a highly mycotrophic species with high levels of fungal colonization. Citrus aurantium rootstocks typically show abundant root colonization by Rhizophagus irregularis three weeks after inoculation. Mycorrhizal symbiosis protects plants against multiple biotic stressors, however, such protection against spider mites remains controversial. We examined mycorrhiza-induced resistance (MIR) in citrus against the two-spotted spider mite Tetranychus urticae. Mycorrhized C. aurantium displayed reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…With regard to the effects of arbuscular mycorrhizal fungi (AMF), previous studies have shown variable effects on spider mites. Spider mite performance was shown to be enhanced by the AMF Glomus mosseae on bean plants [ 30 , 31 , 32 ], whereas spider mite performance in Lotus japonicus was differentially affected by four different AMF species belonging to different genera depending on the AMF species [ 48 ], and negatively affected in citrus plants [ 49 ]. It is evident that this important group of plant-interacting organisms need a more thorough evaluation as putative biocontrol agents.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the effects of arbuscular mycorrhizal fungi (AMF), previous studies have shown variable effects on spider mites. Spider mite performance was shown to be enhanced by the AMF Glomus mosseae on bean plants [ 30 , 31 , 32 ], whereas spider mite performance in Lotus japonicus was differentially affected by four different AMF species belonging to different genera depending on the AMF species [ 48 ], and negatively affected in citrus plants [ 49 ]. It is evident that this important group of plant-interacting organisms need a more thorough evaluation as putative biocontrol agents.…”
Section: Discussionmentioning
confidence: 99%
“…Two-month-old C. reshni and C. aurantium seeds were germinated and grown in vermiculite in a climate chamber with a 16:8 h light/dark photoperiod, 24 °C/18 °C day/night temperature and 50-70% relative humidity (RH). Rhizophagus irregularis (BEG121 isolate) (former Glomus intraradices) was maintained in a soil-based inoculum and inoculated as described by Manresa-Grao et al 44 Control plants were watered once with a filtrate of the mycorrhizal (AM) inoculum, without the AMF spores, to replicate the microbiome. All plants were watered with modified Hoagland's solution; the modification involved the use of a commercial microelements mix (Nutrishell®, Agrimor-Zenagro, Spain), 45 and no pesticide was applied.…”
Section: Plant Materials and Mycorrhizal Inoculationmentioning
confidence: 99%
“…RNA extraction from leaves was performed as described by Kiefer et al, 50 with some modifications indicated in Manresa-Grao et al 44 The RNA concentration was adjusted to 1 μg/μL using a NanoDrop--2000 (Thermo Scientific). Following DNase (Thermo Fisher Scientific) treatment, complementary DNA was obtained using the PrimeScript™ RT Reagent Kit (Takara, Valencia, Spain).…”
Section: Rna Extraction and Quantitative Polymerase Chain Reaction Qu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Priming is a common mechanism during induced systemic resistance triggered by beneficial microbes, consisting of a stronger and faster activation of plant defense mechanisms, usually dependent on jasmonate signaling ( Pieterse et al., 2014 ; Mora-Romero et al., 2014 ; Gruden et al., 2020 ). Despite priming of plant defenses in response to pathogens and herbivores in mycorrhizal plants is well documented ( Campos-Soriano et al., 2012 ; Song et al., 2013 ; Song et al., 2015 ; Sanchez-Bel et al., 2016 ; Fiorilli et al., 2018 ; Schoenherr et al., 2019 ; Sanmartín et al., 2020 ; Rivero et al., 2021 ; Manresa-Grao et al., 2022 ) consequences of AM symbiosis for insect herbivores are complex to predict. Indeed, the nutritional benefits of the symbiosis may increase food availability or improve the diet quality for the pest, depending on the fungal and insect identity and growing conditions ( Koricheva et al., 2009 ; Frew and Price, 2019 ).…”
Section: Introductionmentioning
confidence: 99%